EFFECT OF SUBMAXIMAL EXERCISE ON SYSTOLIC AND DIASTOLIC BLOOD PRESSURE IN YOUNG SEDENTARY NORMOTENSIVE NEPALESE MEDICAL STUDENTS - Arijit Ghosh (Journal of Nepal Medical Association, 2003)
Higher exercise blood pressure represents low cardiorespiratory status of an individual and vice versa. The changes in systolic and diastolic blood pressure in response to rhythmic isotonic muscular exercise in sedentary young normotensive Nepalese students were assessed. Normal blood pressure in standing posture in male and female subjects are about 115 / 75 mm of Hg. and 106 / 71 mm of Hg. respectively. Just after the exercise systolic blood pressure increases moderately in both the sexes, whereas diastolic blood pressure remains unchanged in most of the females. Diastolic blood pressure is found to be decreased slightly in the males, just after exercise. The present study indicates the cardiorespiratory status of the Napalese medical students is within normal range.